2020
DOI: 10.3390/genes11040453
|View full text |Cite
|
Sign up to set email alerts
|

AQP3 Facilitates Proliferation and Adipogenic Differentiation of Porcine Intramuscular Adipocytes

Abstract: The meat quality of animal products is closely related to the intramuscular fat content. Aquaglyceroporin (AQP) defines a class of water/glycerol channels that primarily facilitate the passive transport of glycerol and water across biological membranes. In this study, the AQP3 protein of the AQP family was mainly studied in the adipogenic function of intramuscular adipocytes in pigs. Here, we found that AQP3 was increased at both mRNA and protein levels upon adipogenic stimuli in porcine intramuscular adipocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It was further suggested that melanin genes were involved in the body color variation of red tilapia during overwintering. Eleven known DEGs were shared by BP_PB, BP_WP and PB_WP comparison groups, of which st3gal1, plxna4, fabp11a and aqp3 plays a vital role in regulating cell proliferation, migration and invasion (Wu et al, 2018;Wang et al, 2020). It has been reported that silencing of st3gal1 gene suppresses melanoma invasion and signi cantly reduces the survive ability of aggressive melanoma cells of human in metastatic environment (Pietrobono et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It was further suggested that melanin genes were involved in the body color variation of red tilapia during overwintering. Eleven known DEGs were shared by BP_PB, BP_WP and PB_WP comparison groups, of which st3gal1, plxna4, fabp11a and aqp3 plays a vital role in regulating cell proliferation, migration and invasion (Wu et al, 2018;Wang et al, 2020). It has been reported that silencing of st3gal1 gene suppresses melanoma invasion and signi cantly reduces the survive ability of aggressive melanoma cells of human in metastatic environment (Pietrobono et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among genetic factors, genes can precisely regulate IMF accumulation in skeletal muscle. For instance, AQP3 promoted the proliferation and differentiation of porcine intramuscular preadipocytes [17]. The lipid synthesis was inhibited both in porcine subcutaneous and intramuscular preadipocytes after knockdown of CTRP6 [18].…”
Section: Discussionmentioning
confidence: 98%
“…CD79α plays an important role in B cell development or the activation of downstream signals ( 56 ). AQP3 has a significant effect on the adipogenic differentiation and proliferation of intramuscular adipocytes ( 57 ). JPT2 is a microtubule-associated protein homolog that may have some effects on ASFV DNA and protein accumulation ( 50 ).…”
Section: Discussionmentioning
confidence: 99%